138 Clinicians' Referrals for Stress Echocardiography: Are we Compliant with Nice Guidelines?. (31st May 2014) - Patel, Peysh A; Ravi, Karthik; Kane, Jack; Wass, Eileen; Wilson, Deborah; Carr, Alison; Watchorn, Natasha; Hobman, Raymond Keith; Gill, Donna; Brooksby, William Paul; Kilcullen, Niamh; Artis, Nigel
Abstract : Introduction: Accurate assessment of patients presenting with suspected cardiac pain is of paramount importance as it determines management strategy. Angina itself is a clinical diagnosis and assessing its prognostic significance may require further investigation. NICE provide a framework to aid accurate diagnosis and evaluation (Clinical Guideline 95). Clinicians are encouraged to assess the prognostic significance of underlying coronary disease based on pre-test probability (PTP). Stress Echocardiography (SE) is a non-invasive assessment tool recommended in those patients with a PTP of 30–60%. The primary purpose of this audit was to establish how closely clinicians followed the NICE Clinical Guideline 95 when referring for SE. Furthermore, we wished to evaluate the utility of SE in groups with other PTPs. Methodology: A retrospective analysis of patients referred for SE at Mid Yorkshire Hospitals NHS Trust between March and May 2013 was performed. Consecutive referrals from hospital clinicians within the trust were included, both for exercise and dobutamine testing. Exclusion criteria included referrals for indications other than chest pain and those with established coronary artery disease. Results: 193 patients were evaluated in total. The patients were of a typical demographic profile for suspected coronary disease, with the most common age group being 41–60 (48% of total). 55% were male. 31% were on no anti-anginals prior to referral. 22% (42/193) had typical angina whilst 57% (110/193) described non-anginal pain as judged by the cardiologist supervising the SE. Only 13% (25/193) had a PTP of 30–60%, of which only 16% (4/25) had a positive SE. The most common PTP category was 61–90% (81/193). Of all SE performed, 18% (34/193) were positive. Of these, 56% (19/34) were referred for angiogram and 53% of this cohort (10/19) had angiographically significant lesions requiring intervention. Most interestingly, only 7 of the 110 patients describing non-anginal pain had a positive SE. Of these, 3 were sent for invasive angiography and none required revascularisation. Conclusions: NICE advocates the use of SE for a specific group of patients based on PTP, but a much broader selection across all risk groups are currently being referred within the trust. SE is being performed on patients with non-anginal pain and this should be evaluated in light of such data showing that of 107 patients, not a single one went forward for revascularisation. This accentuates the paramount importance of accurate history-taking and demonstrates clearly that non-anginal presentations confidently exclude flow-limiting lesions and therefore do not require further testing. We advocate similar studies within other trusts to establish whether findings are replicated. Continuing unconsciously outside of NICE guidance is unsustainable on clinical grounds and additionally, it prohibits adequate workforce planning.